Impact of a nurse-led teleconsultation strategy for cardiovascular disease management during COVID-19 pandemic in India: a pyramid model feasibility study. Issue 7 (7th July 2022) - Mohan, Bishav; Singh, Bhupinder; Singh, Kavita; Naik, Nitish; Roy, Ambuj; Goyal, Abhishek; SIngh, Gurbhej; Aggarwal, Shivaansh; Saini, Aftabh; Tandon, Rohit; Chhabra, Shibba Takkar; Aslam, Naved; et al.
Abstract : Objective: The COVID-19 pandemic necessitated the use of telemedicine to maintain continuity of care for patients with cardiovascular diseases (CVDs). This study aimed to demonstrate the feasibility of implementing a nurse-led teleconsultation strategy for CVD management during the COVID-19 pandemic in India and evaluated the impact of nurse-led teleconsultations on patient treatment satisfaction. Design, setting and participants: We developed a two-stage teleconsultation strategy and tested the feasibility of implementing a nurse-led teleconsultation strategy to manage CVD in a northern state (Punjab) in India. A multidisciplinary team of experts developed the treatment protocol used for teleconsultations to manage CVD. Nurses were trained to provide teleconsultation, triaging of patients and referrals to the physicians. Patients with CVD who had an outpatient visit or hospitalisation between September 2019 and March 2020 at the Dayanand Medical College Hospital, Ludhiana, India, were contacted by phone and offered teleconsultations. Telemedicine strategy comprised: stage 1 nurse-led teleconsultations and stage 2 physician-led teleconsultations. Descriptive analysis was performed to report the proportion of patients triaged by the two-stage telemedicine strategy, and patient's clinical characteristics, and treatment satisfaction between the nurse-led versus physician-led teleconsultations. Results: Overall, nurse-led stage 1 teleconsultations were provided to 12 042 patients with CVD. The mean (SD) age of the participants was 58.9 years (12.8), and men were 65.4%. A relatively small proportion of patients (6.3%) were referred for the stage-2 physician-led teleconsultations and of these only 8.4% required hospitalisations. During stage 1 nurse-led teleconsultations, patients were referred to the physicians due to uncontrolled diabetes (24.9%), uncontrolled hypertension (18.7%) and congestive heart failure (16.2%). The patient's treatment satisfaction was similar between the nurse-led versus physician-led teleconsultations (p=0.07). Conclusion: This study showed that a nurse-led telemedicine strategy is feasible to implement in a resource-constraint setting for triaging patients with CVD and reduces physician's burden.